Cover Feature: Additive‐Free Electrophoretic Deposition of Graphene Quantum Dots Thin Films (Chem. Eur. J. 72/2019). Issue 72 (12th November 2019) - Nguyen, Tam D.; Geuli, Ori; Yeo, Loo Pin; Magdassi, Shlomo; Mandler, Daniel; Tok, Alfred Iing Yoong
Abstract : Graphene quantum dots (GQDs) were coated on transparent conductive glass through electrodeposition without using any additive. Their small size and high content of deprotonated carboxylic groups of GQDs enable stability of the dispersion solution for electrodeposition. Surface morphology and physico‐optical properties of this GQDs thin film can be optimized by variation of applied voltage and deposition time. More information can be found in the Full Paper by D. Mandler, A. I. Y. Tok et al. on page 16573 .